Mapping subgenomic promoter of coat protein gene of Cucumber green mottle mosaic virus - Mei LIU; Li-ming LIU; Hui-jie WU; Bao-shan KANG; Qin-sheng GU (Journal of Integrative Agriculture, 2020)
Many plant viruses utilize subgenomic RNA as gene expression strategy, therefore mapping subgenomic promoter (SGP) is extremely important for constructing viral vectors. Although Cucumber green mottle mosaic virus (CGMMV)-based virus vectors have been constructed, SGP of the coat protein (CP) has not yet mapped. To this end, we firstly presumed 13 nucleotides upstream of the start codon as the transcription starting site (TSS) as previous study identified by random amplification of cDNA ends (RACE). Secondly, the region from nucleotides –110 to +175 is the putative CP SGP, as predicted, a long stem loop structure by the secondary structure of RNA covering movement protein (MP) and CP. To map the CGMMV CP SGP, we further constructed a series of deletion mutants according to RNA secondary structure prediction. The deletion of TSS upstream significantly enhanced CP transcription when 105 nucleotides were retained before the CP TSS. For the downstream of CP TSS, we analyzed the expression of enhanced green fluorescent protein (EGFP) in a series of vectors with partial deletion of the CGMMV CP and found that the nucleotides from +71 to +91 played a key role in the EGFP expression at the transcription level, while EGFP showed the highest expression level when 160 nucleotides were retained downstream of the CP TSS. To confirm these results, we applied online software MEME to predict the motifs and cis-acting elements in the 466 nucleotides covering the sequences of deletion analysis. Conserved motifs and relative acting elements were in regions in which transcription levels were the highest or enhanced. To our best knowledge, this is the first mapping of CGMMV SGP.